2018
DOI: 10.3390/bioengineering5010009
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fibers as a Dressing Material for Drug and Biological Agent Delivery in Wound Healing Applications

Abstract: Wound healing is a complex tissue regeneration process that promotes the growth of new tissue to provide the body with the necessary barrier from the outside environment. In the class of non-healing wounds, diabetic wounds, and ulcers, dressing materials that are available clinically (e.g., gels and creams) have demonstrated only a slow improvement with current available technologies. Among all available current technologies, electrospun fibers exhibit several characteristics that may provide novel replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 167 publications
(169 reference statements)
0
84
0
12
Order By: Relevance
“…These properties include a large specific surface area to volume ratio, a porous structure allowing drainage of the wound exudates and permeation of atmospheric oxygen to the wound, superior mechanical performance, and similarity to the nanofibrous structure of extra‐cellular matrix (ECM). In addition to these advantages, electrospinning is compatible with the incorporation of various types of drugs and other drug‐delivery systems to facilitate generation of various composite dressing materials suitable for controlled release of biological agents at different stages of the wound healing process . The combination of nanocontainers with nanofibers by colloid‐electrospinning is an effective tool to develop nanoparticulate composite dressings …”
Section: Introductionmentioning
confidence: 99%
“…These properties include a large specific surface area to volume ratio, a porous structure allowing drainage of the wound exudates and permeation of atmospheric oxygen to the wound, superior mechanical performance, and similarity to the nanofibrous structure of extra‐cellular matrix (ECM). In addition to these advantages, electrospinning is compatible with the incorporation of various types of drugs and other drug‐delivery systems to facilitate generation of various composite dressing materials suitable for controlled release of biological agents at different stages of the wound healing process . The combination of nanocontainers with nanofibers by colloid‐electrospinning is an effective tool to develop nanoparticulate composite dressings …”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds, hydrogel, or other biomaterials have been used as vehicles by providing controlled release of therapeutic agents and tunable release of bioactive molecules of skin engineering [115]. A study has shown that electrospun fibers can be bioactive molecule carriers for wound healing [116]. And a wide variety of bioactive molecules has been incorporated into electrospun fibers and delivered into injured sites.…”
Section: Perspectivesmentioning
confidence: 99%
“…The use of gelatin nanofibers having enough tensile strength for fabricating nonwoven mats has received attention recently for use for antimicrobial applications [45][46][47][48][49]. Successful spinning of minimum diameter nanofibers results in the surface areas of these nanofibers being increased in addition to their light weight.…”
Section: Introductionmentioning
confidence: 99%